2010
DOI: 10.1111/j.1751-7176.2009.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Calcium‐Phosphorus Product With Blood Pressure in Dialysis

Abstract: J Clin Hypertens (Greenwich). 2010;12:96–103. ©2009 Wiley Periodicals, Inc. Hypertension is very common in dialysis patients. Disorders of mineral metabolism have been linked to vascular calcification and hypertension in dialysis. Fifty‐four hemodialysis patients were included in a cross‐sectional study in a dialysis unit during a 6‐month period. Linear regression analysis was done between averages of calcium and phosphorus (ca × ph) product and blood pressures (BPs). Ca × ph was significantly associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Jean et al, also reported similar results in dialysis patients (10). Adragao et al, have publicized that higher vascular calcification scores in dialysis patients were associated with higher mean arterial pressure (11). The total serum calcium x phosphate product is an indicator of the risk of mineral crystallization in soft tissues, (17) which can lead to cutaneous and systemic calciphylaxis, conjunctival precipitation, visceral and in particular, cardiovascular calcification (18).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Jean et al, also reported similar results in dialysis patients (10). Adragao et al, have publicized that higher vascular calcification scores in dialysis patients were associated with higher mean arterial pressure (11). The total serum calcium x phosphate product is an indicator of the risk of mineral crystallization in soft tissues, (17) which can lead to cutaneous and systemic calciphylaxis, conjunctival precipitation, visceral and in particular, cardiovascular calcification (18).…”
Section: Discussionmentioning
confidence: 85%
“…Jean et al concluded that vascular calcifications are highly prevalent in hemodialysis patients and not linked to blood pressure (10). However, Adragao et al conducted a prospective study and concluded that higher vascular calcification scores in dialysis patients were significantly associated with MAP and coronary artery disease (11). In another cross-sectional study conducted by Ashkar, it was cited that calcium phosphorous product (CPP) is positively associated with MAP and unrelated to pulse pressure (12).…”
Section: Introductionmentioning
confidence: 99%
“…Another study from the USA, which studied the relationship between serum phosphate levels and blood pressure in incident hemodialysis patients, found that elevated serum phosphate was associated with higher pre-dialysis SBP and PP with a 1.77 mmHg rise in SBP for each 1 mg/dL higher phosphorous level. Ashkar ZM, in his cross-sectional study, found a significant association between the Ca-P product and pre-dialysis SBP and MAP and both pre and post-dialysis DBP [ 21 ]. No relationship was detected with PP.…”
Section: Discussionmentioning
confidence: 99%
“…The seated cuff (Se) BP goal of <130/80 mm Hg for patients with T2DM was achieved by 62% of the patients after 18 weeks of treatment [53]. Blacks and Hispanics comprised 17 and 26% of the study population, respectively [53], and 81% of the patients had MetS [54]. …”
Section: Recent Olmesartan Medoxomil Efficacy Studies Supporting a Ramentioning
confidence: 99%